PLM education in production design and engineering by e-learning - Kakehi, Munenori; Yamada, Tetsuo; Watanabe, Ichie (International journal of production economics, 2009)
These days more attention is being paid to Product Lifecycle Management (PLM) using a technique for managing total product planning, design, manufacturing, sales, and disposal. We researched business processes and education curriculum of the PLM system in manufacturing businesses. We designed the curriculum of PLM education and developed part of a lesson. Most importantly, e-Learning is shown to be an effective tool for achieving educational objectives. We found that not only knowledge and theory but also practical education methods using case studies in an e-Learning environment are necessary for human resources to develop effective PLM.